URBAN COMMUNITY RESPONSES TO VISUAL APPROPRIATE THEMATIC DESIGN, SUPER HERO PARK BANDUNG - Dian Duhita; Eka Virdianti (Jurnal Pengembangan Kota, 2016)
Parks is one of city public area that serves as a communal place for city community. On another perspective, parks is an architectural design that is designed with an aesthetic element to attract. Bandung, since a few years was to make improvements in various sectors, especially in the public space. Through the slogan Creative City, Bandung City Government revived communities part of the citizens by providing place for a activities, creation and production. Thematic Parks became one of the alternative approaches responsive design as part of creative cities development. Object of research study object is Super Hero park. The purpose of research is to analyzing the response of communities to design a thematic park. The study was conducted with a qualitative approach through participation observation method. The scope of the research includes visual appropriate and city community response. The conclussion obtain that visual appropriate are in accordance with the theme. Urban Community was able to respond well the identity of Super Hero park with visual appropriate design.